The effect of acute caffeine ingestion on endurance performance: A systematic review and meta-analysis - Southward, K.; Rutherfurd-Markwick, J. J.; Ali, A. (Sports Medicine, 2018)
Background: Caffeine is a widely used ergogenic aid with most research suggesting it confers the greatest effects during endurance activities. Despite the growing body of literature around the use of caffeine as an ergogenic aid, there are few recent meta-analyses that quantitatively assess the effect of caffeine on endurance exercise. Objectives: To summarise studies that have investigated the ergogenic effects of caffeine on endurance time-trial performance and to quantitatively analyse the results of these studies to gain a better understanding of the magnitude of the ergogenic effect of caffeine on endurance time-trial performance. Methods: A systematic review was carried out on randomised placebo-controlled studies investigating the effects of caffeine on endurance performance and a meta-analysis was conducted to determine the ergogenic effect of caffeine on endurance time-trial performance. Results: Forty-six studies met the inclusion criteria and were included in the meta-analysis. Caffeine has a small but evident effect on endurance performance when taken in moderate doses (3-6 mg/kg) as well as an overall improvement following caffeine compared to placebo in mean power output (3.03 ± 3.07%; effect size = 0.23 ± 0.15) and time-trial completion time (2.22 ± 2.59%; effect size = 0.41 ± 0.2). However, differences in responses to caffeine ingestion have been shown, with two studies reporting slower time-trial performance, while five studies reported lower mean power output during the time-trial. Conclusion: Caffeine can be used effectively as an ergogenic aid when taken in moderate doses, such as during sports when a small increase in endurance performance can lead to significant differences in placements as athletes are often separated by small margins.